2013
DOI: 10.1016/j.synthmet.2012.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced drug loading capacity of polypyrrole nanowire network for controlled drug release

Abstract: For a conducting polymer (CP) based drug release system, drug loading is often accomplished by a doping process, in which drug is incorporated into polymer as dopant. Therefore, the drug loading capacity is relatively low and the range of drugs can be loaded is limited. In the present work, a polypyrrole (PPy) nanowire network is prepared by an electrochemical method and it is found that the micro-and nanogaps among the individual nanowires of the PPy nanowire network can be used as reservoir to store drugs. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 23 publications
1
48
0
Order By: Relevance
“…The authors report that 100 mV s −1 is an optimal sweep rate to release the anti-inflammatory drug dexamethasone while maintaining the characteristics of the film [108]. Jiang et al [109] found that the sweep rate markedly affects the release of ATP drug from a PPy nanowire network coated by a PPy film considerably. The amount released increased significantly from 57 % to 89 % and 95 % when the system was stimulated at 50, 100 and 200 mV s −1 , respectively, within 10 h. This suggests that the amount of drug released is not directly proportional to the thickness of the film and that the film releases molecules more efficiently from their surface rather than from the bulk of the polymer.…”
Section: Membrane Porosity and Thicknessmentioning
confidence: 99%
“…The authors report that 100 mV s −1 is an optimal sweep rate to release the anti-inflammatory drug dexamethasone while maintaining the characteristics of the film [108]. Jiang et al [109] found that the sweep rate markedly affects the release of ATP drug from a PPy nanowire network coated by a PPy film considerably. The amount released increased significantly from 57 % to 89 % and 95 % when the system was stimulated at 50, 100 and 200 mV s −1 , respectively, within 10 h. This suggests that the amount of drug released is not directly proportional to the thickness of the film and that the film releases molecules more efficiently from their surface rather than from the bulk of the polymer.…”
Section: Membrane Porosity and Thicknessmentioning
confidence: 99%
“…The role of co-vapor in the vapor-phase polymerization (VPP) method was studied [105] An application for drug storage was carried out by depositing PPy using the chemical vapor deposition (CVD) method [106] PEDOT The dependence of electrical conductivity on VPP temperature was discussed [107] Single-crystal CP nanowires were developed using VPP with liquid-bridge-mediated nanotransfer printing [108] A one-step fabrication of 2D nanoparticles was investigated [109] The advantages of directly depositing CP nanofibers was demonstrated [110] Polymers …”
Section: Pani Amyloid Nanofiber Template Polymerizationmentioning
confidence: 99%
“…Facilitating interdisciplinary research will provide new opportunities for CP nanomaterials, and the intelligent integration of the numerous advantages of CPs with other materials has been and will continue to be a key topic in various applications. It is highly anticipated Reprinted with permission from [106]. Copyright 2013, Elsevier.…”
Section: Drug Carriersmentioning
confidence: 99%
“…This has been demonstrated by precisely tuned delivery of the neutral drug progesterone from a PPy scaffold [65]. Further, networks of PPy nanowires were electrochemically prepared in which the micro-and nano-gaps that separated individual PPy nanowires seem to act as drug storage reservoirs [66]. In this system, drug-loading capacity depends on the volume of the micro-and nano-vacancies, and not the doping level.…”
Section: Organic Bioelectronic Active Surfacesmentioning
confidence: 99%
“…In this system, drug-loading capacity depends on the volume of the micro-and nano-vacancies, and not the doping level. Hydrophilic and lipophilic drugs can both be loaded into the micro-and nano-gaps due to the amphilicity of the PPy nanowire network [66].…”
Section: Organic Bioelectronic Active Surfacesmentioning
confidence: 99%